New narrow-range endemic land snails from the sky islands of northern South Africa (Gastropoda: Streptaxidae and Urocyclidae) - Herbert, David G. (European Journal of Taxonomy, 2016)
One new genus and five new species of land snails are described from high altitude, insular, Afrotemperate forest habitats in northern South Africa. The distribution of these species is discussed in relation to other narrowly endemic land snails occurring in this and neighbouring regions. The new genus is Ptilototheca gen. nov.; the five new species are: Gulella davisae sp. nov., G. hadroglossa sp. nov., Ptilototheca soutpansbergensis gen. et sp. nov., Sheldonia monsmaripi sp. nov. and S. wolkbergensis sp. nov.